TINGKAT KEPUASAN PEJALAN KAKI TERHADAP TROTOAR DI KOTA BANDUNG - Rohmawati, Tatik; Natalia, Tri Widianti (JIPSI Jurnal Ilmu Politik dan Komunikasi, 2018)
Bandung is one of the destinations of tourist in Indonesia, especially in the Heritage area which is a historical touristdestination. Jalan Braga has an important role in the development of the city of Bandung, since the Dutch occupation inIndonesia, Jalan Braga has been used as a protocol road in the city of Bandung. It makes the Jalan Braga sidewalkhave an important role for the satisfaction of pedestrian, especially domestic and foreign tourists. The purpose of thisstudy is to find out how the level of pedestrian satisfaction is based on a comparison between the value of perceptionsand expectations of the quality of the elements forming the sidewalks of Jalan Braga, Bandung. This research is adescriptive study with a quantitative approach and uses the Accidential Sampling method in selecting respondents. Themain data of collection method is done by the intercept method. The benefits of this research are to gain knowledgeabout the sidewalk-forming elements that can provide value for comfort and satisfaction for pedestrians. Therefore theGovernment of Bandung City can provide optimal facilities for pedestrians. This can encourage and increase thenumber of pedestrians in the city of Bandung, especially on Jalan Braga which is used as a tourist destination